(untitled) (Bulletin of Innovative Research, 2026)
The article examines the key social factors of code-switching in the speech of contemporary Russian-speaking youth. Determinants such as language prestige, globalization processes, and the influence of internet communication and mass culture are analyzed. Particular attention is paid to the sociolinguistic mechanisms that determine language code choice across different communicative situations. Code-switching is interpreted not only as a linguistic phenomenon but also as a socially conditioned practice reflecting transformations in youth linguistic identity and cultural orientations.